Polyclonal B-cell lymphocytosis with binucleated lymphocytes (PPBL) - Troussard, Xavier (Dove Medical Press, 2008)
Persistent polyclonal B-cell lymphocytosis (PPBL) is a rare and recently described entity. The review of the literature show PPBL is diagnosed predominantly but not exclusively in women, usually smokers. PPBL is recognized by a moderate, chronic and absolute lymphocytosis (>4 × 10(9)/l) in the peripheral blood. In 10% of cases without lymphocytosis, the PPBL diagnosis has to be suggested by peripheral blood examination showing in all cases atypical binucleated lymphocytes. A polyclonal serum IgM is also associated and HLA-DR7 expression is present in most cases. Contrary to B-cell chronic lymphoproliferative disorders (B-CLPD), peripheral B cells are polyclonal with kappa and lambda light-chain expression and no clonal rearrangement of immunoglobulin heavy chain genes is usually demonstrated. The detection of an extra isochromosome for the long arm of chromosome 3 +i(3)(q10) has to be considered as a specific marker of PPBL. We performed conventional cytogenetic analysis (CCA) in 111 patients with typical PPBL we followed-up more than 4 years. +i(3q) was detected in 34% (33/98), PCC in 8% (8/98) and both abnormalities in 31% (30/98). CCA showed neither +i(3q) nor PCC in 28% (27/98). Fluorescence in situ hybridization (FISH) was also performed in 84 cases and +i(3q) was detected in 71% (60/84). When combining both procedures in 84 patients, +i(3q) was detected in 17 patients with negative CCA and was confirmed in 43 patients with positive CCA. CCA and FISH were both negative in 24 cases. Whether patients with PPBL are at increased risk of hematological malignancy remains unclear. After a median follow-up of 4.4 years, most PPBL patients presented a stable clinical and biological course. Six patients died from pulmonary cancer, myocardial infarction, cerebral aneurysm rupture or diffuse large B-cell lymphoma. Two patients had IgM monoclonal gammopathy of undetermined significance (MGUS) at the time of PPBL diagnosis and two other patients developed IgM MGUS respectively 12 and 22 years after PPBL diagnosis. A malignant non Hodgkin's lymphoma (NHL) appeared in 3 additional patients: two patients presented diffuse large B cell lymphoma and 1 patient a splenic marginal zone lymphoma. In conclusion, the possibility of PPBL to evolve toward a clonal proliferation, malignant lymphoma or secondary solid cancer lead us to consider PPBL not as a benign pathology. We recommend a careful and continued clinical and biological long-term follow-up in all PPBL patients.